2000
DOI: 10.1074/jbc.275.6.3873
|View full text |Cite
|
Sign up to set email alerts
|

The ATP Hydrolytic Activity of Purified ZntA, a Pb(II)/Cd(II)/Zn(II)-translocating ATPase from Escherichia coli

Abstract: ZntA, a soft metal-translocating P1-type ATPase from Escherichia coli, confers resistance to Pb(II), Cd(II), and Zn(II). ZntA was expressed as a histidyl-tagged protein, solubilized from membranes with Triton X-100, and purified to homogeneity. The soft metal-dependent ATP hydrolysis activity of purified ZntA was characterized. The activity was specific for Pb(II), Cd(II), Zn(II), and Hg(II), with the highest activity obtained when the metals were present as thiolate complexes of cysteine or glutathione. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
209
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(233 citation statements)
references
References 32 publications
22
209
0
2
Order By: Relevance
“…Due to the chemical similarities between Cu ϩ and Ag ϩ and between Zn 2ϩ and Cd 2ϩ , it is not surprising that P-type exporters specialize in detoxifying one of these two subsets (7,13,14,21,23,24). We have determined the metal specificities for 5 previously uncharacterized P-type transition-metal exporters, along with tentative assignments for 3 additional pumps exhibiting low levels of activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the chemical similarities between Cu ϩ and Ag ϩ and between Zn 2ϩ and Cd 2ϩ , it is not surprising that P-type exporters specialize in detoxifying one of these two subsets (7,13,14,21,23,24). We have determined the metal specificities for 5 previously uncharacterized P-type transition-metal exporters, along with tentative assignments for 3 additional pumps exhibiting low levels of activity.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further supported by functional analysis of various P-type pumps harboring these amino acid motifs. In characterized systems (13,14), pumps harboring amino acid sequences specific to monovalent metals indeed transported only copper and silver, whereas those harboring amino acid sequences specific to divalent metals transported only zinc, cadmium, and lead.To further our understanding of substrate recognition by transition-metal pumps, we have cloned and expressed 18 uncharacterized prokaryotic P-type ATPases (15). Initially, we tested the abilities of the expressed proteins to restore tolerance to external concentrations of copper, silver, zinc, and cadmium in metalsensitive Escherichia coli strains (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cd has been demonstrated to inactivate or denature proteins by binding to sulfhydryl groups, which causes cellular damages by displacing cofactors from a variety of proteins, including transcription factors and enzymes (Goyer, 1997;Sharma et al, 2000;Schützendübel et al, 2001;Lin and Aarts, 2012). Moreover, Cd also induces oxidative stress, which in turn mediates cellular damage in various plants and animals (Shim et al, 2009;Gallego et al, 2012).…”
mentioning
confidence: 99%
“…In addition, a lot of key genes have been shown to be involved in Cd detoxification and tolerance in plants. These include ZNT1, OsHMA9, OsNRAMP5, ZntA, CAD2, AtPDR12, AtPDR8, AtATM3, ACBP1, Nramp5, EIN2, and MAN3 (Pence et al, 2000;Sharma et al, 2000;Shiraishi et al, 2000;Lee et al, 2003Lee et al, , 2007Kim et al, 2006Kim et al, , 2007Xiao et al, 2008;Cao et al, 2009;Lin and Aarts, 2012;Sasaki et al, 2012;Ishikawa et al, 2012;Chen et al, 2015). It was also found that Heat shock transcription factor A4a (HsfA4a) confers Cd tolerance by up-regulating MT gene expression in wheat (Triticum aestivum) and rice (Oryza sativa; Shim et al, 2009).…”
mentioning
confidence: 99%